Polyvinyl alcohol fiber composite material and preparation method thereof

By modifying epoxy resin and polyvinyl alcohol fibers, and using hot press molding, in-situ polymerization and pulsed magnetic field-assisted molding, the problems of insufficient toughness and corrosion resistance in buildings are solved, and the mechanical properties and corrosion resistance of composite materials are significantly improved.

CN119735911AActive Publication Date: 2025-04-01LONG & CONSTR ENG CO LTD +3
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510251702.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-01
Estimated Expiration
2045-03-05

AI Technical Summary

Technical Problem

Due to insufficient toughness and insufficient chemical corrosion resistance in houses and buildings, epoxy resin is difficult to effectively disperse and absorb corrosion in dynamic loads and harsh environments, resulting in cracks or collapse of the building structure.

Method used

By selecting the unsaturated compound methacrylic acid to modify the epoxy resin, the carboxyl group and unsaturated double bonds are added, the polyvinyl alcohol fiber is activated and modified to form a polydopamine coating and silica network structure; and through the process of hot pressing molding, in-situ polymerization and pulsed magnetic field-assisted molding, the fiber-resin interface bonding state is improved.

Benefits of technology

It significantly improves the mechanical properties and corrosion resistance of the composite material, enhances the interface bonding between the fiber and the resin, reduces the possibility of brittle fracture, and improves the overall structural density and acid resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735911A_ABST
    Figure CN119735911A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chemical products, in particular to a polyvinyl alcohol fiber composite material and a preparation method thereof. The problem that the corrosion resistance and the mechanical property of the composite material are poor due to the fact that the interface bonding force between the polyvinyl alcohol fiber and the epoxy resin in the composite material is weak is solved. According to the invention, the epoxy resin is modified by selecting an unsaturated compound methacrylic acid; the preparation method comprises the following steps: activating polyvinyl alcohol fibers, and then modifying the polyvinyl alcohol fibers; an aluminate coupling agent is modified, and active functional groups such as epoxy groups are introduced; and through the processes of primary mixing, in-situ growth, hot press molding, in-situ polymerization and pulsed magnetic field assisted molding, the fiber-resin interface bonding state is improved, and the synergistic effect of all the components is fully exerted, so that the corrosion resistance and the mechanical property of the composite material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical products, in particular to a polyvinyl alcohol fiber composite material and a preparation method thereof. Background Art

[0002] In the field of housing construction, the performance of materials plays a decisive role in the quality, safety and durability of buildings. With the continuous improvement of people's requirements for building quality and the continuous development of construction technology, the demand for high-performance building materials has become more urgent. As a commonly used building material, epoxy resin has a wide range of applications in housing construction due to its excellent adhesion, chemical corrosion resistance and good mechanical properties. For example, it can be used to reinforce and repair building structures to improve the bearing capacity of damaged structures; it can also be used as a floor coating to enhance the wear resistance and corrosion resistance of the ground. However, epoxy resin itself still has some obvious shortcomings: its toughness is insufficient, and it is prone to brittle failure when facing dynamic loads such as earthquakes and wind loads. It cannot effectively disperse and absorb energy, resulting in cracks in the building structure or even collapse; in addition, although epoxy resin has a certain resistance to chemical corrosion, its corrosion resistance is still insufficient in the face of some harsh environments, such as acid rain and industrial wastewater. After long-term contact, problems such as coating shedding and structural damage may occur.

[0003] In order to improve the performance of epoxy resin, fiber reinforcement technology has become a research hotspot. Polyvinyl alcohol fiber has high strength, high modulus, good flexibility and certain chemical stability. The use of polyvinyl alcohol fiber reinforced epoxy resin composites in house construction can enhance the seismic resistance, deformation resistance and corrosion resistance of building structures. However, there are some problems in the actual application of this composite material. The interface bonding force between polyvinyl alcohol fiber and epoxy resin is weak, and the stress cannot be effectively transferred between the fiber and the matrix, which makes the mechanical properties and corrosion resistance of the composite material limited.

[0004] Therefore, a polyvinyl alcohol fiber composite material and a preparation method thereof are proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a polyvinyl alcohol fiber composite material and a preparation method thereof, wherein the epoxy resin is modified by selecting an unsaturated compound methacrylic acid; the polyvinyl alcohol fiber is activated and then modified; the aluminate coupling agent is modified to introduce active functional groups such as epoxy groups; and the fiber-resin interface bonding state is improved through the processes of primary mixing, in-situ growth, hot pressing molding and in-situ polymerization and pulsed magnetic field assisted molding, and the synergistic effect of each component is fully exerted, so that the corrosion resistance and mechanical properties of the composite material are improved.

[0006] To achieve the above object, the present invention provides the following technical solutions: It should be noted that all parts in the present invention are parts by mass.

[0007] One aspect of the present invention provides a method for preparing a polyvinyl alcohol fiber composite material, and the preparation method is as follows: S1: initial mixing: adding the modified epoxy resin, modified polyvinyl alcohol fiber, nano-silica, toughening agent and modified coupling agent into a planetary ball mill and mixing them at a speed of 400 rpm for 1.5 h to obtain a mixture 1; S2 in-situ growth: add 15-20 parts of tetraethyl orthosilicate and 0.9 parts of hydrochloric acid to mixture 1, and carry out hydrolysis and polycondensation reaction at 55°C for 5 hours to obtain mixture 2; S3 hot pressing and in-situ polymerization: transfer the mixture 2 to a hot pressing mold, add 15-20 parts of methyl methacrylate and 0.3 parts of benzoyl peroxide, and then hot press to form the mixture. In-situ polymerization of the monomer is initiated under hot pressing conditions, so that the polymer is simultaneously generated in the network structure of the modified polyvinyl alcohol fiber and nano-silicon dioxide to obtain a hot pressing material. S4 pulse electric field assisted molding: the hot pressed material is transferred to the mold, and a pulse electric field is applied at a temperature of 130°C and a pressure of 10MPa at the same time, with an electric field strength of 5-10kV / cm and a pulse frequency of 15Hz for 15min to obtain a polyvinyl alcohol fiber composite material; The modified epoxy resin is obtained by reacting epoxy resin E51, methacrylic acid, azobisisobutyronitrile, triphenylphosphine and N,N-dimethylbenzylamine; The modified coupling agent is obtained by surface grafting glycidyl methacrylate onto an aluminate coupling agent; The modified polyvinyl alcohol fiber is obtained by reacting activated polyvinyl alcohol fiber with an initiator solution.

[0008] Preferably, the preparation method of activated polyvinyl alcohol fiber is as follows: 50 parts of polyvinyl alcohol fiber are placed in a mixed solution containing dopamine and trivalent iron ions, and oscillated at 30-40°C for 3-4 hours. After the reaction is completed, rinse with deionized water until neutral to obtain activated polyvinyl alcohol fiber; the dopamine concentration is 2.5g / L; the trivalent iron ion concentration is 0.2g / L; the total amount of the mixed solution is 100 parts.

[0009] Preferably, the preparation method of modified polyvinyl alcohol fiber is as follows: add 3 parts of sodium p-styrene sulfonate to 80 parts of deionized water and stir to dissolve, add 0.3 parts of potassium persulfate thereto to obtain an initiator solution; add 25 parts of activated polyvinyl alcohol fiber to a reactor containing the initiator solution and seal it, heat it to 55°C, start stirring, react at a speed of 200 rpm for 3-6 hours, rinse with deionized water, put it in a vacuum drying oven at 60°C and dry it to constant weight to obtain modified polyvinyl alcohol fiber.

[0010] Preferably, the preparation method of the modified epoxy resin is as follows: 100 parts of epoxy resin E51 are added to a three-necked flask, 160 parts of acetone are added thereto, and the mixture is stirred at a temperature of 45° C. and a speed of 400 rpm for 15 min to obtain an epoxy resin solution; 15-30 parts of methacrylic acid and 0.5-1 part of azobisisobutyronitrile are mixed evenly, and then added dropwise to the epoxy resin solution at a speed of 2 drops / s, and the temperature is raised to 75° C. while the addition is continued, and then 0.8-1.8 parts of triphenylphosphine and 0.5 parts of N, N-dimethylbenzylamine are added, and the reaction is continued for 4.5 hours, and then reduced pressure distillation is performed to obtain the modified epoxy resin.

[0011] Preferably, the hot pressing molding temperature in S3 is 110° C., the pressure is 10 MPa, and the time is 21-31 min.

[0012] Preferably, the preparation method of the modified coupling agent is as follows: 50 parts of aluminate coupling agent and 10-20 parts of glycidyl methacrylate are added to a three-necked flask containing 100 parts of toluene, stirring is started at a stirring speed of 350 rpm, the temperature is raised to 80° C., benzoyl peroxide is added thereto, the reaction is carried out for 3.5-5.5 hours, the mixture is cooled to room temperature, and the toluene is removed by reduced pressure distillation to obtain a modified coupling agent.

[0013] On the other hand, the present invention provides a polyvinyl alcohol fiber composite material, which is prepared by any one of the above-mentioned preparation methods; the raw materials used in the production of the polyvinyl alcohol fiber composite material include 50-70 parts of modified epoxy resin, 20-30 parts of modified polyvinyl alcohol fiber, 10 parts of nano-silicon dioxide, 5 parts of toughening agent terminal carboxyl liquid nitrile rubber and 1-3 parts of modified coupling agent.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] 1. The present invention uses unsaturated compound methacrylic acid to modify epoxy resin, thereby introducing active groups such as carboxyl and unsaturated double bonds into the epoxy resin. The carboxyl can undergo esterification reaction with the hydroxyl group on the surface of the polyvinyl alcohol fiber to form hydrogen bonds or ester bonds, thereby enhancing the interfacial bonding force between the fiber and the resin. The unsaturated double bonds can participate in subsequent polymerization reactions, thereby further increasing the crosslinking density of the resin and improving the mechanical properties of the composite material. In addition, the introduction of methacrylic acid destroys the originally relatively rigid molecular structure of the epoxy resin to a certain extent, increases the flexibility of the molecular chain, and reduces the possibility of brittle fracture of the composite material when subjected to stress.

[0016] 2. The present invention activates polyvinyl alcohol fiber, and dopamine undergoes self-polymerization reaction on the fiber surface under the catalysis of alkaline environment and trivalent iron ions to form a polydopamine coating, which not only enhances the surface activity of the fiber, but also has a certain anti-corrosion ability; then the active groups on the polydopamine coating on the fiber surface are used to react with sodium p-styrene sulfonate, and the sulfonic acid group has strong acidic environment tolerance. After being grafted to the fiber surface, the stability of the fiber in an acidic corrosive environment can be effectively improved, and the compatibility with epoxy resin can be better; at the same time, the silica network structure formed by in-situ growth is wrapped on the fiber surface, and the nano-silica, fiber and epoxy resin matrix are tightly connected, the fiber-resin interface bonding state is improved, the density of the internal structure of the material is increased, the pores and defects are reduced, and the intrusion channel of the corrosive medium is reduced.

[0017] 3. The present invention prepares a modified coupling agent, grafts glycidyl methacrylate onto an aluminate coupling agent, and introduces active functional groups such as epoxy groups into the coupling agent. The epoxy groups can react with the hydroxyl groups on the fiber surface to establish a strong chemical bridge between the fiber and the resin, thereby significantly enhancing the interfacial bonding force, enabling the composite material to more effectively transfer stress when subjected to force and improving the mechanical properties. By controlling the amount of modified epoxy resin, modified polyvinyl alcohol fiber and modified coupling agent, the synergistic effect of each component can be further enhanced.

[0018] 4. The present invention adopts a process of simultaneous hot pressing and in-situ polymerization. During the hot pressing process, the monomer methyl methacrylate is in-situ polymerized under the action of an initiator, and the polymer is simultaneously generated in the network structure composed of polyvinyl alcohol fibers, nano-silicon dioxide and epoxy resin, so that the synergistic effect between the components can be fully exerted, and the polymer chains are entangled with the fibers, resins, etc., further enhancing the interfacial adhesion. The pulsed electric field is used to promote the orientation of the molecular chains, further improve the fiber-resin interface state, and improve the crystallinity of the composite material, thereby enhancing the mechanical properties and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The present invention is a process flow chart for preparing a polyvinyl alcohol fiber composite material. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] See also Figure 1The present invention provides a polyvinyl alcohol fiber composite material and a preparation method thereof, and the technical scheme is as follows: Depend on Figure 1 It can be seen that the polyvinyl alcohol fiber composite material in the present invention is obtained by initially mixing modified epoxy resin, modified polyvinyl alcohol fiber, nano-silica, toughening agent and modified coupling agent, and then undergoing in-situ growth, hot pressing molding and in-situ polymerization and pulse electric field assisted molding.

[0022] The substance information involved in the present invention is as follows: Ethyl orthosilicate CAS: 78-10-4; Hydrochloric acid CAS: 7647-01-0; Methyl methacrylate CAS: 80-62-6; Benzoyl peroxide CAS: 94-36-0; Polyvinyl alcohol fiber CAS: 9002-89-5; Dopamine CAS: 51-61-6; Sodium p-styrene sulfonate CAS: 2695-37-6; Potassium persulfate CAS: 7727-21-1; Epoxy resin E51 CAS: 61788-97-4; acetone CAS: 67-64-1; methacrylic acid CAS: 79-41-4; azobisisobutyronitrile CAS: 78-67-1; triphenylphosphine CAS: 603-35-0; N,N-dimethylbenzylamine CAS: 103-83-3; glycidyl methacrylate CAS: 106-91-2; toluene CAS: 108-88-3; nano-silica was purchased from Xuancheng Jingrui New Materials Co., Ltd.; aluminate coupling agent was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.; carboxyl-terminated liquid nitrile rubber was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.

[0023] Example 1

[0024] S1: initial mixing: 50 parts of modified epoxy resin, 20 parts of modified polyvinyl alcohol fiber, 10 parts of nano-silicon dioxide, 5 parts of toughening agent carboxyl-terminated liquid nitrile rubber and 1 part of modified coupling agent were added into a planetary ball mill and mixed at a speed of 400 rpm for 1.5 hours to obtain a mixture 1; S2 in-situ growth: 15 parts of tetraethyl orthosilicate and 0.9 parts of hydrochloric acid were added to mixture 1, and a hydrolysis and polycondensation reaction was carried out at 55°C for 5 hours to obtain mixture 2; S3 hot pressing and in-situ polymerization: Transfer the mixture 2 to a hot pressing mold, add 15 parts of methyl methacrylate and 0.3 parts of benzoyl peroxide, and then hot press. In-situ polymerization of the monomer is initiated under hot pressing conditions, so that the polymer is simultaneously generated in the network structure of the modified polyvinyl alcohol fiber and nano-silica to obtain a hot pressing material; the hot pressing temperature is 110°C, the pressure is 10MPa, and the time is 21min; S4 pulse electric field assisted molding: The hot pressed material is transferred to the mold, and a pulse electric field is applied at the same time under the conditions of temperature of 130°C and pressure of 10MPa. The electric field strength is 5kV / cm and the pulse frequency is 15Hz. The polyvinyl alcohol fiber composite material is obtained after processing for 15 minutes.

[0025] The preparation method of the modified epoxy resin is as follows: 100 parts of epoxy resin E51 are added into a three-necked flask, 160 parts of acetone are added thereto, and the mixture is stirred at 400 rpm for 15 min at a temperature of 45° C. to obtain an epoxy resin solution; 15 parts of methacrylic acid and 0.5 parts of azobisisobutyronitrile are uniformly mixed, and then added dropwise into the epoxy resin solution at a rate of 2 drops / s, and the temperature is raised to 75° C. while the addition is continued, and then 0.8 parts of triphenylphosphine and 0.5 parts of N, N-dimethylbenzylamine are added, and the reaction is continued for 4.5 hours, and then the modified epoxy resin is obtained by vacuum distillation.

[0026] The preparation method of modified polyvinyl alcohol fiber is as follows: 50 parts of polyvinyl alcohol fiber are placed in a mixed solution containing dopamine and trivalent iron ions, and oscillated at 30°C for 3 hours. After the reaction is completed, it is rinsed with deionized water to neutrality to obtain activated polyvinyl alcohol fiber; the dopamine concentration is 2.5 g / L, and the trivalent iron ion concentration is 0.2 g / L; 3 parts of sodium p-styrene sulfonate are added to 80 parts of deionized water and stirred to dissolve, and 0.3 parts of potassium persulfate are added thereto to obtain an initiator solution; 25 parts of activated polyvinyl alcohol fiber are added to a reactor containing the initiator solution and sealed, the temperature is raised to 55°C, stirring is started, and the reaction is carried out at a speed of 200 rpm for 3 hours. After rinsing with deionized water, it is placed in a vacuum drying oven at 60°C and dried to constant weight to obtain modified polyvinyl alcohol fiber; the total amount of the mixed solution is 100 parts; the trivalent iron ions come from ferric chloride.

[0027] The preparation method of the modified coupling agent is as follows: 50 parts of aluminate coupling agent and 10 parts of glycidyl methacrylate are added to a three-necked flask containing 100 parts of toluene, stirring is started at a speed of 350 rpm, the temperature is raised to 80°C, benzoyl peroxide is added thereto, the reaction is carried out for 3.5 hours, the mixture is cooled to room temperature, and the toluene is removed by reduced pressure distillation to obtain a modified coupling agent.

[0028] Embodiment 2-5 Referring to the preparation method and parameter conditions of Example 1, the specific differences are shown in Table 1.

[0029] Comparative Example 1 The preparation method and parameter conditions are the same as those of Example 4, except that the epoxy resin is not modified.

[0030] Comparative Example 2 The preparation method and parameter conditions are the same as those of Example 4, except that the epoxy resin E51 is replaced by the epoxy resin E44.

[0031] Comparative Example 3 The preparation method and parameter conditions are the same as those of Example 4, except that N,N-dimethylbenzylamine was not added when preparing the modified epoxy resin.

[0032] Comparative Example 4 The preparation method and parameter conditions are the same as those of Example 4, except that triphenylphosphine is not added when preparing the modified epoxy resin.

[0033] Experimental Example 1 Mechanical Properties Test The mechanical properties of the composite materials were tested according to the standard of GB / T 1449-2005; the results are shown in Table 1.

[0034] Table 1 Mechanical properties of Examples 1-5 and Comparative Examples 1-4

[0035] As can be seen from Table 1, in Examples 1-5, by selecting the unsaturated compound methacrylic acid to modify the epoxy resin, active groups such as carboxyl and unsaturated double bonds are introduced into the epoxy resin, and the carboxyl group can react with the hydroxyl group on the surface of the polyvinyl alcohol fiber to form a hydrogen bond or an ester bond, thereby enhancing the interfacial bonding force between the fiber and the resin, and the unsaturated double bond can participate in the subsequent polymerization reaction, further increasing the crosslinking density of the resin and improving the mechanical properties of the composite material; and the introduction of methacrylic acid destroys the relatively rigid molecular structure of the epoxy resin to a certain extent, increases the flexibility of the molecular chain, and reduces the possibility of brittle fracture of the composite material when subjected to stress. In Example 4, when the amount of methacrylic acid is 20 parts, the amount of azobisisobutyronitrile is 0.7 parts, and the amount of triphenylphosphine is 1.3 parts, the mechanical properties of the composite material obtained are the best, and the bending strength is 220MPa. In Comparative Example 1, the epoxy resin was not modified, and its reactivity with the fiber and the coupling agent was low, the interfacial bonding strength was insufficient, and when subjected to stress, debonding easily occurred between the fiber and the resin, and the stress could not be effectively transferred, resulting in a decrease in the mechanical properties of the composite material. In Comparative Example 2, the epoxy resin E51 was replaced by the epoxy resin E44, and the cross-linked structure was relatively loose, which affected the interfacial bonding and overall performance, resulting in a decrease in the mechanical properties of the composite material. In Comparative Examples 3-4, when preparing the modified epoxy resin, N, N-dimethylbenzylamine or triphenylphosphine was not added, and the two could not have a synergistic effect, and the reaction was not sufficiently carried out. The content of active groups in the modified epoxy resin was relatively low, resulting in a decrease in its reactivity with the fiber and the coupling agent, which hindered the internal stress transfer and energy dissipation of the composite material when subjected to stress, resulting in a decrease in mechanical properties.

[0036] Embodiment 6-10 Referring to the preparation method and parameter conditions of Example 4, the specific differences are shown in Table 2; in Table 2, temperature and time 1 are the temperature and time when the polyvinyl alcohol fiber is activated, and time 2 is the time for modifying the activated polyvinyl alcohol fiber.

[0037] Comparative Example 5 The preparation method and parameter conditions are the same as those of Example 7, except that the polyvinyl alcohol fibers are not activated.

[0038] Comparative Example 6 The preparation method and parameter conditions are the same as those of Example 7, except that the activated polyvinyl alcohol fiber is not modified.

[0039] Comparative Example 7 The preparation method and parameter conditions are referred to in Example 7, except that the in-situ growth in the preparation step S2 is not performed, but the mixture obtained in S1 is directly subjected to hot pressing and in-situ polymerization in S3.

[0040] Experimental Example 2 Corrosion resistance test The composite material was immersed in a 10% hydrochloric acid solution until the composite material showed signs of cracking, collapse, etc., then the experiment was terminated and the erosion time was recorded. The results are shown in Table 2.

[0041] Table 2 Corrosion resistance test of Example 4, Examples 6-10 and Comparative Examples 5-7

[0042] As can be seen from Table 2, in Example 4 and Examples 6-10, by activating the polyvinyl alcohol fiber, dopamine will undergo a self-polymerization reaction on the fiber surface under the catalysis of alkaline environment and trivalent iron ions to form a polydopamine coating, which can not only enhance the surface activity of the fiber, but also has a certain anti-corrosion ability; then, the active groups on the polydopamine coating on the fiber surface are used to react with sodium p-styrene sulfonate, and the sulfonic acid group has strong acidic environment tolerance. After being grafted to the fiber surface, the stability of the fiber in an acidic corrosive environment can be effectively improved, and the compatibility with epoxy resin can be better; at the same time, the silica network structure formed by in-situ growth is wrapped on the fiber surface, and the nano-silica, fiber and epoxy resin matrix are tightly connected, the fiber-resin interface bonding state is improved, the density of the internal structure of the material is increased, the pores and defects are reduced, and the intrusion channel of the corrosive medium is reduced. In Example 7, when the temperature of the activated polyvinyl alcohol fiber is 36°C, the time is 3.6h, the time of modifying the activated polyvinyl alcohol fiber is 5.0h, and the amount of tetraethyl orthosilicate used during in-situ growth is 18 parts, the fiber-resin interface bonding state is optimal, and the obtained composite material has the best corrosion resistance, and the acid resistance time is 120 days. In Comparative Example 5, the polyvinyl alcohol fiber is not activated, the fiber surface activity is insufficient, the combination with the resin and the coupling agent is not tight, pores and microcracks are easily formed at the interface, and the corrosive medium can penetrate into the composite material through the interface defects, and react chemically with the fiber and the resin, resulting in a decrease in fiber strength, swelling or degradation of the resin matrix, thereby reducing the corrosion resistance of the composite material. In Comparative Example 6, the activated polyvinyl alcohol fiber is not modified, and the fiber surface lacks functional groups such as sulfonic acid groups, so that the interface bonding between the fiber and the resin is not strong enough, and the corrosive medium is more likely to diffuse between the fiber and the resin, accelerating the corrosion of the material. The silica network structure has a certain chemical stability and can serve as a barrier to prevent further intrusion of corrosive media. In Comparative Example 7, the in-situ growth in preparation step S2 was not carried out, and the silica network structure was not formed. The composite material lost this effective protective layer, allowing the corrosive media to more easily reach the fiber and resin matrix, thereby reducing the corrosion resistance of the composite material.

[0043] Examples 11-15 Referring to the preparation method and parameter conditions of Example 7, the specific differences are shown in Table 3; the reaction time in Table 3 is the reaction time when preparing the modified coupling agent.

[0044] Comparative Example 8 The preparation method and parameter conditions are the same as those of Example 12, except that the coupling agent is not modified.

[0045] Comparative Example 9 The preparation method and parameter conditions are the same as those of Example 12, except that modified polyvinyl alcohol fiber is not added.

[0046] Comparative Example 10 The preparation method and parameter conditions are the same as those of Example 12, except that no modified coupling agent is added.

[0047] Experimental Example 3 Mechanical Properties Test The mechanical properties of the composite materials were tested according to the standard of GB / T 1449-2005; the results are shown in Table 3.

[0048] Table 3 Mechanical properties test of Example 7, Examples 11-15 and Comparative Examples 8-10

[0049] As shown in Table 3, in Example 7 and Example 11-15, by preparing a modified coupling agent, glycidyl methacrylate is grafted onto an aluminate coupling agent, and active functional groups such as epoxy groups are introduced into the coupling agent. The epoxy groups can react with the hydroxyl groups on the fiber surface, and a strong chemical bridge is established between the fiber and the resin, thereby significantly enhancing the interfacial bonding force, so that the composite material can more effectively transfer stress when subjected to force, and improve the mechanical properties; by controlling the amount of modified epoxy resin, modified polyvinyl alcohol fiber and modified coupling agent, the synergistic effect of each component can be further improved. In Example 12, when the amount of glycidyl methacrylate is 16 parts when preparing the modified coupling agent, the reaction time is 4.5h, the amount of modified epoxy resin is 60 parts, the amount of modified polyvinyl alcohol fiber is 26 parts, and the amount of modified coupling agent is 2.0 parts, the mechanical properties of the composite material obtained are the best, and the bending strength is 226MPa. In Comparative Example 8, the coupling agent was not modified, and the coupling agent could not form effective chemical bonding or physical adsorption with the modified epoxy resin, modified polyvinyl alcohol fiber and nano-silicon dioxide, which would lead to stress concentration at the interface when subjected to force, making it easy for the composite material to slide or separate relative to each other when subjected to external force, thereby reducing the overall mechanical properties of the composite material. In Comparative Example 9, the modified polyvinyl alcohol fiber was not added, and the composite material lacked this important reinforcing phase, and could not improve the overall mechanical properties through the bearing capacity of the fiber, resulting in a significant reduction in the bending strength of the composite material. In Comparative Example 10, the modified coupling agent was not added, and it was difficult to form a good interaction and synergistic working mechanism between the phases. The composite material could not give full play to the advantages of each phase when subjected to force, and the mechanical properties would be limited.

[0050] Examples 16-20 Referring to the preparation method and parameter conditions of Example 12, the specific differences are shown in Table 4.

[0051] Comparative Example 11 Referring to the preparation method and parameter conditions of Example 16, the difference is that in the preparation step S3, hot pressing molding is performed first, and then in-situ polymerization is performed. The specific steps are as follows: the mixture 2 is transferred to a hot pressing mold for hot pressing molding. The hot pressing molding temperature is 110°C, the pressure is 10 MPa, and the hot pressing time is 25 min to obtain a hot pressing intermediate product; then the hot pressing intermediate product is added to a reactor, 18 parts of methyl methacrylate and 0.3 parts of benzoyl peroxide are added, and an in-situ polymerization reaction is performed at 80°C. The in-situ polymerization pressure is 0.5 MPa, and the time is 60 min to obtain a hot pressed material.

[0052] Comparative Example 12 Referring to the preparation method and parameter conditions of Example 16, the difference is that in preparation step S3, in-situ polymerization is carried out first, and then hot pressing is carried out. The specific steps are as follows: 18 parts of methyl methacrylate and 0.3 parts of benzoyl peroxide are added to mixture 2, and an in-situ polymerization reaction is carried out at 80°C. The in-situ polymerization pressure is 0.5 MPa, and the time is 60 min to obtain an in-situ polymerization product; then the in-situ polymerization product is moved to a hot pressing mold for hot pressing molding. The hot pressing molding temperature is 110°C, the pressure is 10 MPa, and the hot pressing time is 25 min to obtain a hot pressed material.

[0053] Comparative Example 13 The preparation method and parameter conditions are similar to those of Example 16, except that pulsed electric field-assisted molding is not used.

[0054] Comparative Example 14 The preparation method and parameter conditions are the same as those of Example 16, except that the pulse frequency is 30 Hz.

[0055] Comparative Example 15 The preparation method and parameter conditions are the same as those of Example 16, except that the pulse frequency is 5 Hz.

[0056] Experimental Example 4 Corrosion resistance test: immerse the composite material in a 10% hydrochloric acid solution until the composite material is cracked, collapsed or otherwise damaged. The test is terminated and the corrosion time is recorded. Mechanical properties test: The mechanical properties of the composite materials were tested according to the standard GB / T 1449-2005. The results are shown in Table 4.

[0057] Table 4 Corrosion resistance test of Example 12, Examples 16-20 and Comparative Examples 11-15

[0058] As can be seen from Table 4, in Example 12 and Example 16-20, by adopting the process of simultaneous hot pressing and in-situ polymerization, during the hot pressing process, the monomer methyl methacrylate is in-situ polymerized under the action of the initiator, and the polymer is simultaneously generated in the network structure composed of polyvinyl alcohol fiber, nano-silicon dioxide and epoxy resin, so that the synergistic effect between the components is fully exerted, the polymer chain is entangled with the fiber, resin, etc., and the interfacial bonding force is further enhanced; the orientation arrangement of the molecular chain is promoted by the pulse electric field, the fiber-resin interface state is further improved, and the crystallinity of the composite material is improved, and the mechanical properties and corrosion resistance are enhanced. In Comparative Examples 11-12, hot pressing and in-situ polymerization are carried out separately, which will lead to the insufficient tightness and uniformity of the combination between the polymer and the fiber and nanoparticles, and the interface bonding force is weakened, so that the composite material is prone to problems such as interface debonding when subjected to external force, and the mechanical properties are reduced; and there are more defects and pores inside the material, which become channels for the penetration of corrosive media, accelerate the corrosion of the material, and reduce the corrosion resistance. In Comparative Example 13, pulse electric field-assisted molding was not used, the regularity and orderliness of the internal structure of the material may be poor, and the mechanical properties are difficult to reach the optimal state; the density of the material is low, and the corrosive medium is more likely to enter the interior of the material and react chemically with the material, resulting in a decrease in the corrosion resistance of the material. In Comparative Example 14, the pulse frequency is 30Hz. Too high a pulse frequency will cause the molecular chains inside the material to move too violently, which is not conducive to the orderly arrangement and stable combination of the molecular chains, and the internal structure of the material becomes unstable or produces more defects, resulting in a decrease in the mechanical properties and corrosion resistance of the composite material. In Comparative Example 15, the pulse frequency is 5Hz, and the electric field does not act sufficiently on the molecular chains inside the material, and cannot effectively promote the orientation and arrangement of the molecular chains. The structural regularity and density of the material are difficult to be effectively improved, which will also reduce the mechanical properties and corrosion resistance of the composite material.

[0059] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a polyvinyl alcohol fiber composite material, characterized in that: The preparation method is as follows: S1: initial mixing: adding modified epoxy resin, modified polyvinyl alcohol fiber, nano-silica, toughening agent and modified coupling agent into a ball mill and mixing them at a speed of 400 rpm for 1.5 h to obtain a mixture 1; S2 in-situ growth: 15-20 parts of tetraethyl orthosilicate and 0.9 parts of hydrochloric acid were added to the mixture one, and a hydrolysis and polycondensation reaction was carried out at 55° C. for 5 hours to obtain a mixture two; S3 hot pressing and in-situ polymerization: the mixture is transferred to a hot pressing mold, 15-20 parts of methyl methacrylate and 0.3 parts of benzoyl peroxide are added, and hot pressing is performed, and the monomer is initiated to polymerize in situ under hot pressing conditions to obtain a hot pressing material; S4 pulse electric field assisted molding: the hot pressed material is transferred to a mold, and a pulse electric field is applied at a temperature of 130° C. and a pressure of 10 MPa at the same time, with an electric field strength of 5-10 kV / cm, for 15 minutes to obtain the polyvinyl alcohol fiber composite material; The modified epoxy resin is obtained by reacting epoxy resin E51, methacrylic acid, azobisisobutyronitrile, triphenylphosphine and N,N-dimethylbenzylamine; The modified coupling agent is obtained by surface grafting reaction of glycidyl methacrylate on an aluminate coupling agent; The modified polyvinyl alcohol fiber is obtained by reacting activated polyvinyl alcohol fiber with an initiator solution.

2. The method for preparing a polyvinyl alcohol fiber composite material according to claim 1, characterized in that: The preparation method of the activated polyvinyl alcohol fiber is as follows: 50 parts of the polyvinyl alcohol fiber are placed in a mixed solution containing dopamine and trivalent iron ions, and oscillated at 30-40° C. for 3-4 hours. After the reaction is completed, the fiber is rinsed with deionized water until it is neutral to obtain the activated polyvinyl alcohol fiber; the dopamine concentration is 2.5 g / L; the trivalent iron ion concentration is 0.2 g / L.

3. The method for preparing a polyvinyl alcohol fiber composite material according to claim 1, characterized in that: The preparation method of the modified polyvinyl alcohol fiber is as follows: 3 parts of sodium p-styrene sulfonate are added to 80 parts of deionized water and stirred to dissolve, and 0.3 parts of potassium persulfate are added thereto to obtain the initiator solution; 25 parts of the activated polyvinyl alcohol fiber are added to a reaction kettle containing the initiator solution and sealed, the temperature is raised to 55°C, stirring is started, and the reaction is carried out at a speed of 200 rpm for 3-6 hours, and after rinsing with the deionized water, the fiber is placed in a vacuum drying oven at 60°C and dried to constant weight to obtain the modified polyvinyl alcohol fiber.

4. The method for preparing a polyvinyl alcohol fiber composite material according to claim 1, characterized in that: The preparation method of the modified epoxy resin is as follows: 100 parts of the epoxy resin E51 are added into a three-necked flask, acetone is added thereto, and the mixture is stirred at a temperature of 45° C. and a rotation speed of 400 rpm for 15 minutes to obtain an epoxy resin solution; 15-30 parts of methacrylic acid and 0.5-1 part of azobisisobutyronitrile are uniformly mixed, and then dripped into the epoxy resin solution at a speed of 2 drops / s, and the temperature is raised to 75° C. while dripping, and then 0.8-1.8 parts of triphenylphosphine and 0.5 parts of N, N-dimethylbenzylamine are added, and the reaction is continued for 4.5 hours, and then reduced pressure distillation is performed to obtain the modified epoxy resin.

5. The method for preparing a polyvinyl alcohol fiber composite material according to claim 1, characterized in that: The hot pressing molding temperature in S3 is 110° C., the pressure is 10 MPa, and the time is 21-31 min.

6. The method for preparing a polyvinyl alcohol fiber composite material according to claim 1, characterized in that: The preparation method of the modified coupling agent is as follows: 50 parts of the aluminate coupling agent and 10-20 parts of the glycidyl methacrylate are added to a three-necked flask filled with 100 parts of toluene, stirring is started at a stirring speed of 350 rpm, the temperature is raised to 80° C., the benzoyl peroxide is added thereto, the reaction is carried out for 3.5-5.5 hours, the mixture is cooled to room temperature, and the toluene is removed by reduced pressure distillation to obtain the modified coupling agent.

7. A polyvinyl alcohol fiber composite material, characterized in that: The polyvinyl alcohol fiber composite material is prepared by the preparation method described in any one of claims 1 to 6; the raw materials used in the production of the polyvinyl alcohol fiber composite material include 50-70 parts of modified epoxy resin, 20-30 parts of modified polyvinyl alcohol fiber, 10 parts of nano-silicon dioxide, 5 parts of toughening agent terminal carboxyl liquid nitrile rubber and 1-3 parts of modified coupling agent.

Citation Information

Patent Citations

  • Pre-preg, fiber-reinforced composite material, and thermoplastic resin particles

    CN104955883A

  • High-modulus polyvinyl alcohol fiber reinforced PPO / PA6 alloy and preparation method thereof

    CN107418186A

  • Method for producing a thermodeformable polymer / fiber composite

    CN112601644A

  • Method for producing epoxy resin

    JP2010116521A

  • Adhesion promoters for glass-containing systems

    US20060045967A1